2022
DOI: 10.3390/app122211747
|View full text |Cite
|
Sign up to set email alerts
|

Curve of Spee and Second Mandibular Premolar Agenesis—Present Knowledge and Future Perspectives

Abstract: Background: We investigated the relationship between the mandibular Curve of Spee (COS) and a persisting primary second mandibular molar (ppM2) due to an agenesis of the second mandibular premolar, using a digital software technique. Methods: Digital dental casts were obtained from 200 patients at the Department of Orthodontics in Innsbruck and Vienna, Austria. Patients (age-, gender-, and malocclusion-matched) were equally divided into two groups (n = 100) according to the existence of a ppM2. COS depth, over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The research conducted by Schieffer et al [16] demonstrates the importance of regulating COS in prosthetic rehabilitations, particularly in cases that involve long-span restorations. This is achieved through a multidisciplinary strategy that combines knowledge from prosthodontics and orthodontics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research conducted by Schieffer et al [16] demonstrates the importance of regulating COS in prosthetic rehabilitations, particularly in cases that involve long-span restorations. This is achieved through a multidisciplinary strategy that combines knowledge from prosthodontics and orthodontics.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the COS is inherently connected to the measurement of overjet and overbite in the diagnosis and treatment of malocclusion [14]. Studies have shown that there is a direct relationship between the depth of the COS and an increased horizontal overlap of the upper and lower teeth (overjet) [15] as well as an increased vertical overlap of the front teeth (overbite), especially in cases where there is a Class II malocclusion [5,16]. The depth of the COS directly impacts the horizontal and vertical overlapping of the teeth.…”
Section: Of 16mentioning
confidence: 99%